Mating patterns in a savanna population of valley oak, Quercus lobata Neé - Sork, V. L.; Davis, F. W.; Dyer, R. J.; Smouse, P. E. (Fifth Symposium on Oak Woodlands, 2002)
California Valley oak is threatened by landscape alteration and failing recruitment in remnant stands. Its reproductive ecology is a key element of the seedling recruitment process. We first examine the mating system, to determine the extent of inbreeding in a population at Sedgwick Reserve, in Santa Barbara County. We then quantify variation in germination success and acorn size, evaluating their spatial patterns across the site. We collected acorns from 21 mapped focal trees in fall 1999, measured their average seed weight and germination success, and identified their multilocus genotypes. Using a mixed mating model, we observed significant, but modest selfing (outcrossing rate: tm = 0.96) and no mating among relatives (tm – ts) = 0.0. The effective pollen donor number was estimated to be between 5 and 7 individuals, depending on the inbreeding coefficient of the adults. These mating results indicate relatively little inbreeding but low numbers of pollen donors. Mothers differed significantly in seed weight (range: ~ 4 - 10 g) and germination percentage (range: 0 – 90 percent), and a bivariate analysis showed a gradient across the study site. Such a pattern suggests that environment conditions influence acorn size and germination success. Future work will address whether isolated individuals are at risk of selfing, for the expression of inbreeding depression on seed traits, or a reduction in the effective pollen donor number.